Avaliação dos possíveis efeitos antipsicóticos da Alpinia zerumbet em camundongo - Araújo, Fernanda Yvelize Ramos de (2011)
Alpinia zerumbet (Pers.), zingiberaceae family, is a species known in Brazil as a colony. The essential oil of Alpinia zerumbet (OEAZ) extracted from leaves of the plant has been evaluated in classic animal models of drug screning with activity in anxiety, depression, seizures, psychosis and antioxidant, such as the open field, rota rod, tail suspension, forced swimming, plus-maze, seizures induced by electroshock, evaluation of apomorphine-induced stereotypy and ketamine-induced hyperlocomotion tests and neurochemical analysis through the dopamine concentration, as well as the antioxidant evaluation of the OEAZ in vitro by nitrite levels. The OEAZ was administered intraperitoneally into mice (males) at 50 and 100 mg / kg doses. The results showed that OEAZ in open field test increased locomotor activity, as well as the grooming, but it decreased the rearing quantity, suggesting an effect on the dopaminergic system. In the rota rod test it had no effect on motor coordination in animals. The OEAZ showed up with a depressant action on the central nervous system (CNS), because in the forced swimming and tail suspension tests increased the immobility time in animals. In the plus-maze test it did not alter the mice performance suggesting that the essential oil in the doses used did not appears to have anxiolytic / anxiogenic activities. The essential oil of Alpinia zerumbet showed the highest dose (100mg/kg) anticonvulsant effect with decrease tonic clonic seizures, this action may be directly linked to the oil constituents, as monoterpenos. The oil was able to revert to a dose–dependent manner apomorphine-induced stereotyped behavior, strongly indicating the involvement of dopamine receptors in the oil activity, a hypothesis confirmed by the decrease of the neurotransmitters levels in the striatal dopamine levels. As for the ketamine-induced hyperlocomotion, the OEAZ reduced locomotor activity, these data can be explained as resulting from blocked dopamine receptors. Regarding the antioxidant action, OEAZ was able to return the nitrite levels to normal parameters. In conclusion these results showed that the OEAZ had important effects on behavior that is based on actions attributed mainly to inhibition dopamine receptors.